Functional Impairment in Children With Externalizing Behavior Disorders: Psychometric Properties of the Weiss Functional Impairment Rating Scale–Parent Report in a German Clinical Sample. Issue 13 (November 2019) - Dose, Christina; Hautmann, Christopher; Doepfner, Manfred
Objective: To examine the psychometric properties of a German adaptation of the Weiss Functional Impairment Rating Scale–Parent Report (WFIRS-P) in a clinical sample of children (4-12 years) with externalizing behavior disorders.Method: Data were collected within two clinical trials ( N = 264). Factorial validity, reliability, and divergent validity from symptoms of ADHD and oppositional defiant disorder (ODD) were assessed.Results: Confirmatory factor analyses revealed that a bifactor model consistent with the theoretical assumption of a general construct of impairment (total scale) and additional specific factors (subscales) provided satisfactory data fit. Model-based reliability estimates showed that both the general construct and specific factors accounted for item variance. Internal consistencies were >.70, part–whole corrected item–scale correlations mostly >.30. Correlations between the WFIRS-P Scales and ADHD and ODD symptoms were low to moderate.Conclusion: The results support the factorial validity, reliability, and divergent validity of the WFIRS-P.